CLAUSEWITZ’S THEORY ON WAR IN THE FIGHT AGAINST INSURGENCY (COIN): IS IT STILL VALID? (Journal of the Spanish Institute for Strategic Studies, 2018)
Following the bloody attacks on Washington and New York on September11, 2001, the United States got involved in a Global War onTerror, GWOT, leading military forces to insist on dedicating most oftheir human resources and materials in the fight against Islamist fanaticismand extremism throughout the world, in particular in Afghanistanand Iraq. But the need to confront this specific type of adversary in thesetwo scenarios, and within its particular context, led the armed forcesto adopt a special form of military power, different from that which hadtraditionally been used to face a conventional adversary.Thus, the war on insurgency (COIN) in the last decade became themain focus for the American armed forces and for those from otherwestern countries, with multiple implications in the organizational anddoctrinal fields, and, above all, in the change of mindset of its participants,more prone to combat an adversary in symmetric terms, andwith the application of maximum strength combat for a rapid and total destruction. In short, it meant a change in the paradigm of the preferreduse of force in the military culture, and the way to wage war by themembers of Western armies, particularly of the United States.Therefore, the adoption of what may be called the “COIN paradigm”has dominated the action of the American armed forces to fulfill theirmission in Afghanistan and Iraq up to the strategic change imposedby the Obama administration in 2012, moment in which there was aredirection of priorities of the essential postulates of the security anddefense policy of the United States toward the Asia-Pacific scenario.This has led one to question the current validity of the general principlesidentified in armed conflicts throughout history; in other words,the fundamentals of the theory on war that have controlled the organization,preparation, and equipment of armies in the past.This article intends to analyze the persistence of the nature of war inits traditional concept, within the context of the COIN paradigm, asthe form of conflict that prevails presently. To do so, the theory of warof the famous Prussian philosopher Carl von Clausewitz, published inhis major work On War, has been used as a basis for this study. Writtenduring the first half of the 19th century, in light of his experiences andreflections about the Napoleonic campaigns, it is still a required referencefor all studies regarding the nature of war. This theory is analyzedin view of the basic principles of today’s predominant adversary: insurgency,with COIN as the strategy to combat it.The hypothesis for the development of this analysis is that war, in thesense of the struggle between the will of two adversaries to prevail,through the use of force, has intrinsic principles and a logic that areidentifiable and can also be extended to the dynamics which are characteristicof a COIN struggle. The analysis undertaken will lead tothe development of conclusions regarding the degree of applicabilityof the premises characteristic of a theory of war, such as the one of thefamous Clausewitz in the struggle against insurgency and, with it, ifthe theory of the brilliant Prussian is still valid in a COIN context. Inshort, whether the death certificate of the famous Prussian should beissued, or he is still alive and in good health.